Disaster mitigation education: Efforts to improve school community disaster preparedness - Rachman, Indriyani; Fumitoshi, Murae; Yayoi, Kodama (Education and Development Research, 2024)
Indonesia is one of the countries frequently affected by natural disasters, including land, air, and sea disasters. Government efforts to socialize disaster mitigation education have been extensive across various sectors of society. However, the results have not yet met the expected targets. In Japan, a country frequently hit by numerous disasters, disaster mitigation education is integrated into the curriculum. At least twice a year, students undergo disaster preparedness drills. This aims to make students responsive when disasters strike suddenly. A trial of disaster mitigation education was conducted, focusing on understanding the surrounding environment by identifying hazardous and safe areas and interviewing residents to gather information about past disasters in their area. Subsequently, students were taught to prepare emergency kits, create eating utensils, and develop learning materials like story cards, similar to practices in Japanese elementary schools. Data was collected from 500 questionnaires distributed to elementary school teachers in Mataram. The trial materials were tested in each class, and teachers were interviewed afterward. The results showed that some teachers taught disaster mitigation to students, resulting in increased understanding among students about what to do when facing disasters. Classroom teachers stated that disaster preparedness drills were meaningful activities for students because they needed to be trained not to panic during disasters.